P019 Paediatric Crohn's disease patients in remission have a reduced skeletal muscle protein balance after feeding. (16th January 2018) - Walker, A; Nixon, A; Cordon, S; Marshall, M; Yeo, M; Devadason, D; Muhammed, R; Tsintzas, K; Kirkham, S; Stephens, F; Moran, G
Abstract: Background: Sarcopenia is common in active Crohn's disease (CD) and still prevalent in remission. This can lead to fatigue, physical inactivity and poor quality of life. The aetiology is unclear. Low levels of physical activity, inability to respond to anabolic stimuli such as food (anabolic resistance, AR) and insulin resistance (IR) could all be implicated in the failure of CD patients in remission to re-build muscle mass. We aimed to investigate the association between sarcopenia and AR and IR, and the role of physical activity in age, gender matched children with CD. Methods: 18 fasted, male and female CD patients (on thiopurines ± anti-TNF alpha) in deep remission (16y, BMI=21) and 9 matched controls (Con) (16y, BMI=21) drank a liquid meal (Ensure plus, 44 g CHO, 14 g PRO, 11 g fat) at t = 0. Arterialised hand and venous forearm blood samples were collected concurrently and brachial artery blood flow measured at baseline and every 20 min for 2 h. Net balance of branched-chain amino acids (BCAA) and glucose were derived, providing indices of skeletal muscle protein balance and IR. Participants had a DEXA scan and handgrip dynamometer test on the day, and wore a pedometer and completed a food diary (each for 3 days) to assess physical activity and food intake. Patient-related outcome measure questionnaires (incl. IBD-fatigue) were completed. Results: CD and Con exhibited an initial response to feeding by increasing BCAA flux: Con from 0.3 ± 0.5 μmol/min at t = 0 to 1.1 ± 0.7 μmol/min at t = 20, and CD from −0.8 ± 0.4 μmol/min at t = 0 to 0.8 ± 0.3 μmol/min at t = 20. This positive response was only sustained beyond t = 60 in Con, such that net BCAA balance across the 2 h was lower in CD (0.6 ± 0.3 vs. −0.1 ± 0.2 μmol/min, respectively, p = 0.05). IBD-fatigue scores indicated CD suffer from moderate fatigue (6.2), which had a moderate effect on daily activities (16.7). Handgrip dynamometer testing showed a trend towards greater fatigue in CD vs. Con (+8 %points) in the dominant arm ( p = 0.061). A trend towards lower total body lean mass in CD (−15%, p = 0.084) was found. No differences were detected in strength, physical activity, diet or IR. In summary: despite not exhibiting AR, as they initially responded to the meal stimulus, CD could not maintain a positive protein balance post feeding compared with Con. This was associated with reduced muscle mass and function. Conclusions: The inability to sustain a positive protein balance postprandially could provide an explanation for the reduced muscle mass seen in CD patients in remission. This could be contributing to fatigue and poor muscle function. Pharmacological interventions to reduce protein breakdown and a high-protein diet to improve the anabolic response to food could both be investigated as potential treatments.